Micro-Influencer Celebrity’s Communication Strategy in Brand Promotion - Silalahi, Ayuphita Tiara (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research analyzed the role of Instagram influencers, especially those who fell into the category of microinfluencers, and the impacts they generated through effective communication strategy in promoting local brands in Indonesia. The exploratory study adopted a qualitative research design by collecting primary data through indepth interviews with selected micro-influencers, local brands marketers, and an Influencer marketing strategist. While secondary data was gathered from both offline and online available documented literatures. Results were then categorized using Creswell’s six-stage analysis method in order to produced themes. Findings show that Instagram is a preferred social media platform in Indonesia for local companies to promote their brands by selecting micro-influencers as part of the communication strategy. Four distinctive characteristics outline the themes of Instagram micro-influencer that are seen as primary factors for the brands to utilize in ensuring effective brands’ communication strategy. The research concludes that different methods of delivering a brand’s messages can be utilized to achieve the brand’s communication goals and the high intensity of engagement between the influencer and their followers is the core strength for the success of the communication activity. This is a quality seeks by both brands and influencer agencies to ensure successful brands’ communication strategy.